Design of inorganic polymer composites for electromagnetic radiation absorption using potassium titanates - Lebedev, V. V.; Miroshnichenko, D. V.; Nyakuma, B. B.; Moiseev, V. F.; Shestopalov, O. V.; Vyrovets, S. V. (Сумський державний університет, 2023)
This paper investigated the synthesis of inorganic polymer composites for electromagnetic radiation absorption using potassium titanates. The selected polyamide 6 and potassium polytitanate materials contain TiО2, K2СО3, and KCl obtained by charge sintering. Results showed that modification of polyamide 6 with sintering products in the form of a fine powder of potassium polytitanate that contains different phases K2O × 2TiO2, K2O × 4TiO2, and K2O × 6TiO2 which increased their strength properties. With increased potassium titanates (PTT) synthesis, a gradual transition from di to potassium hexatitanates occurs K2O × 2TiO2 – K2O × 4TiO2 – K2O × 6TiO2. The optimal content of potassium polytitanate was over 20 % by mass. To fully ensure the reinforcing effect due to the filling of potassium polytitanate polyamide 6, it is necessary to use whiskers K2O × 6TiO2, which can be collected by the additional crystallization of the amorphous charge sintering product. By designing experimental statistical mathematical models in equal regressions, mathematical optimization of inorganic polymer composites for electromagnetic radiation absorption using PTT was carried out.
Keywords: polymer; composite; potassium titanates; synthesis; electromagnetic radiation; absorption; strength properties